Entrepreneurship Education and Social Entrepreneurial Intentions: The Mediating Effects of Entrepreneurial Social Network - Hassan, H. M. Kamrul; Igel, Barbara; Shamsuddoha, Mohammad (Frontiers in Psychology, 2022)
Throughout recent years, social entrepreneurship has received considerable recognition from universities. This study aimed to examine the mediating effect of the entrepreneurial social network on entrepreneurship education and social entrepreneurial intention (SEI) of students at the university level. This study adopted a cross-sectional quantitative approach. A self-administered questionnaire was used to collect responses from a randomly selected sample of students studying at the undergraduate and postgraduate levels in the public and private universities of Bangladesh who were exposed to entrepreneurship education. The data were then analyzed through partial least squares structural equation modeling (PLS-SEM). Results revealed a significant positive relationship between entrepreneurship education and students' social entrepreneurial intention on the one hand and between entrepreneurship education and entrepreneurial social network on the other hand. It was also found that entrepreneurial social networks had a significantly positive link with students' SEIs. Furthermore, the study found that entrepreneurial social networks significantly mediate the relationship between entrepreneurship education and students' SEI. Based on these outcomes, it is suggested to further pay attention to entrepreneurship education and strengthen the entrepreneurial social network to enhance SEI among students. Research findings have provided valuable insights regarding how entrepreneurship education can significantly impact SEI and emphasize the importance of entrepreneurial social networks as a mediator in social entrepreneurship. This study aims to contribute to the relevant social entrepreneurial literature by providing insights on practical issues related to the role of the entrepreneurial social network at the entrepreneurship education level.